A Comparison of Sŏngho Yi Ik's Understanding of the Heart-mind with Matteo Ricci's Understanding of the Soul - Kim, Hanna (Acta Koreana, 2025)
This study argues that Simsŏl 心說 (Exposition on the heart-mind) by Sŏngho Yi Ik 星湖 李瀷 (1681–1763) follows the traditional Neo-Confucian understanding of the heart-mind. Based on the structural similarity between the three layers of the heart-mind—plant, animal, and human—in his writings and in those of the Jesuit order, much previous research has claimed that he was influenced by Western learning. Although the hierarchy of plant, animal, and human first appeared in the Xunzi 荀子, it is accepted by Zhu Xi 朱熹, and is included in the Sŏngni taejŏn 性理大全 (Compendium on nature and principle). Sŏngho’s articulation of the heart-mind followed Neo-Confucian ideas. He acknowledged that the heart-mind of plants is an allegory that refers to the existence of a pattern-principle in the world. He also described the function of the heart-mind in terms of a consciousness, zhijue 知覺 (K. chigak), that in animals, tends to like profit and hate loss, while in humans, it informs their sense of right and wrong. In contrast, Matteo Ricci rejected the Xunzian hierarchy of the myriad being and instead characterized living things in terms of their possession of a soul and found human beings to be unique in terms of their possession of an immortal soul, comprised of reason and free will. While Western learning may have been an inspiration for Sŏngho in composing Simsŏl, his work followed a Neo-Confucian understanding of the heart-mind. KCI Citation Count: 0